Short-term Changes in Quality of Life among Women Who had Hysterectomy for Benign Indications at Young Age: A preliminary study - Mohd Azri Mohd Suan; Seema Sehgal; Edahayati Ahmad Tajudin; Huan Keat Chan; Kunasegaran Kannaiah (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: The objective of this study was to compare the quality of life scores between younger (≤ 45 years old) and older women (≥ 46 years old) who underwent hysterectomy for benign indications. Materials and Methods: A prospective cohort study was performed at a tertiary hospital over a 12-week period. Younger and older women who underwent elective hysterectomy for benign indications were selected as study and control groups, respectively. Quality of life was measured using the Malay version of the World Health Organisation Quality of Life Assessment-BREF questionnaire. The difference in quality of life scores from pre-surgery to 12 weeks post-hysterectomy between the two age groups were measured using repeated-measures analysis of variance (ANOVA).results: A total of 18 women were enrolled in the study group and 45 in the control group. Except for the environment domain among control group, all other domains showed an improvement in quality of life scores. However, the group-time interaction of the repeated-measures ANOVA showed no difference in quality of life score changes of all domains between younger and older women following hysterectomy. Conclusion: In this preliminary study, younger women demonstrated comparable quality of life scores at 12 weeks after hysterectomy in comparison with older women. The results of this study may assist the gynaecologist and patient during pre-surgery counselling.